Sanitation of stainless steel and other food-preparation surfaces - Frank, Joseph F.; Chimielewski, Revis A. N. (Technical series (Nickel Development Institute (Canada)) ;, 1997)
This book describes of effectiveness of sanitation with quaternary ammonium compound or chlorine on stainless steel and other domestic food-preparation surfaces.